2021
DOI: 10.5588/ijtld.20.0574
|View full text |Cite
|
Sign up to set email alerts
|

Measuring TB drug levels in the hair in adults and children to monitor drug exposure and outcomes

Abstract: INTRODUCTION: Testing for anti-TB drugs in small hair samples may serve as a non-invasive tool to measure cumulative drug exposure and/or adherence, as these determine treatment success. We aimed to assess how well hair assays of TB drugs predict TB treatment outcomes.METHODS: A small thatch of hair, ~30 strands, was cut from the occipital region in adults and children from a prospective TB cohort in India. Isoniazid (INH), acetyl-INH and pyrazinamide (PZA) were extracted from the hair samples and quantified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 0 publications
0
14
0
Order By: Relevance
“…Acting upon such delays may be of benefit in India, where PWT face challenges in reaching clinics to collect their medication refills [ 4 ]. Measuring drug metabolites in other specimens such as hair may also be valuable, although these assays may be more costly than urine testing [ 40 ]. In addition, given that ~11% of people with TB in India without a prior treatment history (ie, “new cases”) have isoniazid-monoresistant disease [ 41 ], point-of-care drug metabolite testing approaches need to be developed for other TB drugs.…”
Section: Discussionmentioning
confidence: 99%
“…Acting upon such delays may be of benefit in India, where PWT face challenges in reaching clinics to collect their medication refills [ 4 ]. Measuring drug metabolites in other specimens such as hair may also be valuable, although these assays may be more costly than urine testing [ 40 ]. In addition, given that ~11% of people with TB in India without a prior treatment history (ie, “new cases”) have isoniazid-monoresistant disease [ 41 ], point-of-care drug metabolite testing approaches need to be developed for other TB drugs.…”
Section: Discussionmentioning
confidence: 99%
“…Once there, we (R.A. and A.R.R.) extracted and quantified INH and acetyl INH (a metabolite that is dependent on host acetylation status) in the hair samples using the isotope dilution method (internal standards: INH-d4 and acetyl-INH-d4) by LC-MS/MS [ 22 , 23 ].…”
Section: Methodsmentioning
confidence: 99%
“…Our survey showed that progress in TDM is being made, with half of the survey participants using TDM. Cheaper and easy to use assays [9][10][11], clinical guidelines [2][3][4] and laboratory quality control standards [12] are all increasing in availability. However, the main challenge is a lack of widespread information about TDM, with progress being recognised by participants who look towards guidelines and research when performing TDM.…”
Section: Https://isgd/tdmsurveymentioning
confidence: 99%